2010
DOI: 10.3844/ajassp.2010.969.975
|View full text |Cite
|
Sign up to set email alerts
|

Approximation of Iteration Number for Gauss-Seidel Using Redlich-Kister Polynomial

Abstract: Problem statement: Development of mathematical models based on set of observed data plays a crucial role to describe and predict any phenomena in science, engineering and economics. Therefore, the main purpose of this study was to compare the efficiency of Arithmetic Mean (AM), Geometric Mean (GM) and Explicit Group (EG) iterative methods to solve system of linear equations via estimation of unknown parameters in linear models. Approach: The system of linear equations for linear models generated by using least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The high correlation suggests a linear function for the subordinate color channels in terms of base color (Y= a*X +b). The following steps are used to compute the approximate coefficients a and b for V and W color channels (Hasan et al, 2010):…”
Section: Selection Of Base Colormentioning
confidence: 99%
“…The high correlation suggests a linear function for the subordinate color channels in terms of base color (Y= a*X +b). The following steps are used to compute the approximate coefficients a and b for V and W color channels (Hasan et al, 2010):…”
Section: Selection Of Base Colormentioning
confidence: 99%
“…In addition to these functions, only one study has been explored to investigate the application of the Redlich-Kister approximation function in the numerical analysis particularly on constructing the mathematical model. For instance, in [25], the authors investigated the construction of two mathematical models based on the piecewise third-order Redlich-Kister polynomial model and the piecewise first-order polynomial model respectively to show the relationship of the number of iterations for Gauss-Seidel towards its corresponding grid size. The findings of their work concluded that the results of the piecewise third-order Redlich-Kister polynomial model gave highly accurate solutions as compared with the firstorder polynomial solution.…”
Section: Introductionmentioning
confidence: 99%